Steel gate to freedom : the life of Liu Xiaobo - Yu, Jie, 1973- (Rowman and Littlefield, 2015)
Chinese activist Liu Xiaobo-awarded the Nobel Peace Prize while serving an eleven-year prison sentence-has helped shatter longstanding barriers to freedom of organization and expression in China. This biography, written by one of his closest friends, retraces Liu Xiaobo's inspiring life, from his childhood years to his current imprisonment.